Manifestations of intraocular inflammation over time in patients on brolucizumab for neovascular AMD - Khoramnia, Ramin; Figueroa, Marta S.; Hattenbach, Lars-Olof; Pavésio, Carlos E.; Anderesi, Majid; Schmouder, Robert; Chen, Yu; de Smet, Marc D. (Graefe's archive for clinical and experimental ophthalmology, 2021)
To describe the adverse events associated with brolucizumab, in particular the sequence of intraocular inflammation (IOI), retinal vasculitis (RV), and/or retinal vascular occlusion (RO).
Gesehen am 27.06.2023